2004
DOI: 10.1128/jb.186.3.611-622.2004
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Expression of the Mannose-Resistant Fimbriae of Photorhabdus temperata K122 during Insect Infection

Abstract: Photorhabdus temperata K122 is an entomopathogenic bacterium symbiotically associated with nematodes of the family Heterorhabditidae. Surface fimbriae are important for the colonization of many pathogenic bacteria, and here we report the nucleotide sequence and analysis of the expression of a 12-kbp fragment encoding the mannose-resistant fimbriae of P. temperata (mrf). The mrf gene cluster contains 11 genes with an organization similar to that of the mrp locus from Proteus mirabilis. mrfI (encoding a putative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…This latter observation could be related to alteration of virulence, as it has been recently suggested that MrfA plays an important role in the pathogenic process of Photorhabdus temperata (39). In P. luminescens, the luxS-deficient strain exhibited an attenuated and delayed pathogenicity, consistent with the reduced virulence observed in luxS-deficient strains of Neisseria meningitidis, Streptococcus pneumoniae, and Vibrio vulnificus (32,64,77).…”
Section: Vol 72 2006 Pleiotropic Role Of Ai-2 In Photorhabdus Luminsupporting
confidence: 67%
“…This latter observation could be related to alteration of virulence, as it has been recently suggested that MrfA plays an important role in the pathogenic process of Photorhabdus temperata (39). In P. luminescens, the luxS-deficient strain exhibited an attenuated and delayed pathogenicity, consistent with the reduced virulence observed in luxS-deficient strains of Neisseria meningitidis, Streptococcus pneumoniae, and Vibrio vulnificus (32,64,77).…”
Section: Vol 72 2006 Pleiotropic Role Of Ai-2 In Photorhabdus Luminsupporting
confidence: 67%
“…The mrx operon consists of five structural genes (mrxACDGH) and one putative regulatory gene, mrxJ. BLAST analysis revealed that the mrx genes were most closely similar to the mrp and mrf orthologous genes of Proteus mirabilis (Zhao et al, 1997) and Photorhabdus temperata (Meslet-Cladiere et al, 2004), respectively (Fig. 1).…”
Section: Sequence Analysis Of the Mrx Operonmentioning
confidence: 99%
“…Notably, MrpJ paralogs are not restricted to P. mirabilis as they have been detected in fimbrial operons from related genera (264266). Because fimbriae allow bacteria to adhere or form biofilms in specific environments, and thus respond to niche-specific signals, MrpJ paralogs have been proposed to orchestrate genetic programs that are beneficial to those environments (132, 267).…”
Section: Virulence Factorsmentioning
confidence: 99%